1994
DOI: 10.1002/bjs.1800810346
|View full text |Cite
|
Sign up to set email alerts
|

Cancer of the colon and rectum in Ghana: A 5-year prospective study

Abstract: A prospective study of 134 patients who presented to a teaching hospital in Ghana for the first time with colorectal cancer between January 1987 and December 1991 is reported. The mean number of new patients per year was nearly three times that of a decade ago. The disease afflicts both sexes equally and the age of highest incidence is in the seventh and eighth decades. Some 65 patients had colonic cancer and 69 rectal lesions. Most patients presented with advanced disease and only four of 109 in whom disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 15 publications
5
25
0
Order By: Relevance
“…In a large study involving 16,433 symptomatic cases who underwent flexible sigmoidoscopy over a 16 year period in a single colorectal unit in south of England, it was shown that the chance of missing a proximal lesion with this procedure is about 2.5% (Thompson et al, 2008). In West Africa about 50% of colorectal cancers are located in the rectum of which 78% are within reach of the examining finger, with another 20% in the sigmoid, descending and splenic flexure of the colon (Dakubo et al, 2010;Irabor and Adedeji, 2009;Naaeder and Archampong, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In a large study involving 16,433 symptomatic cases who underwent flexible sigmoidoscopy over a 16 year period in a single colorectal unit in south of England, it was shown that the chance of missing a proximal lesion with this procedure is about 2.5% (Thompson et al, 2008). In West Africa about 50% of colorectal cancers are located in the rectum of which 78% are within reach of the examining finger, with another 20% in the sigmoid, descending and splenic flexure of the colon (Dakubo et al, 2010;Irabor and Adedeji, 2009;Naaeder and Archampong, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Since the last report on colorectal cancer from this centre in 1994 10 tracking of new colorectal cancer cases seen at the centre was maintained. Records of cases seen at the endoscopy unit and the four general surgical wards where these patients were admitted and treated were evaluated prospectively.…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…The epidemiological pattern of the disease varies markedly between different populations group [9] Colorectal cancer is the third most common malignancy in both men and women worldwide [1] and the second most frequent cause of death in the Western Europe and America [1]. In Africa, this disease was considered to be rare but this is no longer true [2].…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal Cancer is an important disease with a large morbidity and mortality rate worldwide [1,2] .The etiology of colorectal cancer appears to be multifactorial in role especially diet with high fat content [3] . Change in diet and lifestyle contributes to risk of developing colorectal cancer as described in a study by Elias Degiannis et al, where he found that there was an increased incidence of polyps proven histologically in association with colorectal carcinoma in affluent people (14%) who have acquired westernized lifestyle as compared with people with poor rural lifestyle (5.5%) [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation